Pareto and Pure Economics - Ricci, Umberto (Review of Economic Studies, 1933)
Journal Article Pareto and Pure Economics Get access Umberto Ricci Umberto Ricci Gizeh University, Cairo Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 1, Issue 1, October 1933, Pages 3–21, https://doi.org/10.2307/2967433 Published: 01 October 1933